Numerical modeling of seismic performance of gravity quay wall. Issue 1 (February 2021) - Aldelfee, Alaa N.; Aldefae, Asad H.; Zubaidi, Salah. L.
Abstract: The main important factor that has to be considered by the designers during the preliminarily design stage of quay walls in ports is uunderstanding the mechanism of the damages that occurs during earthquakes. Increasing of seismic disasters occurrence during recent decades leads to increase the attention during this stage. For this purpose, Finite element modeling is performed to investigate the seismic performance of gravity quay wall (caisson). Plaxis 2D software is used to simulate seismic behavior of real gravity quay wall (i.e. Kobe harbor quay wall) using single frequency earthquake motion. The response of the acceleration and the seismic displacement of the quay wall are simulated. The shaking table tests of two models of the quay wall in dry and saturated conditions were compared with the results of numerical modeling. The results showed that the seismic wave amplification is increased significantly from the foundation of the gravity quay wall to the surface of the model, in which the highest amplification happened at the top of the quay wall model. It was observed that the Plaxis-2d finite element models is an effective tool to predict the seismic performance of the quay wall and there was clear agreement between both the results of experimental results and numerical modeling.